2019
DOI: 10.1002/app.47914
|View full text |Cite
|
Sign up to set email alerts
|

High‐density polyethylene membranes embedded with carboxylated and polyethylene glycol‐grafted nanodiamond to be used in membrane bioreactors

Abstract: In this work, neat and modified nanodiamond (ND) particles were embedded into high-density polyethylene (HDPE) membranes to improve hydrophilicity and antifouling properties. The membranes were prepared via thermally induced phase separation (TIPS) method and used for pharmaceutical wastewater treatment in membrane bioreactors (MBR) system. To prevent the agglomeration of ND, it was modified using two methods: thermal carboxylation (ND-COOH) and grafting with polyethylene glycol (ND-PEG). Membranes with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It can be observed that the hydrophilicity of membranes increased continuously by the additional ND-COOH and ND-PEG nanoparticles and all nanocomposite membranes exhibit less contact angle than pure membrane (127°). This increment in the hydrophilicity of nanocomposite membranes could be due to the existence of hydrophilic functional groups on the surface of the nanoparticles (Etemadi et al, 2017b;Kivi et al, 2019). Membranes with 0.75 wt.% of NPs showed the minimum contact angles.…”
Section: Hydrophilicity and Porositymentioning
confidence: 98%
See 1 more Smart Citation
“…It can be observed that the hydrophilicity of membranes increased continuously by the additional ND-COOH and ND-PEG nanoparticles and all nanocomposite membranes exhibit less contact angle than pure membrane (127°). This increment in the hydrophilicity of nanocomposite membranes could be due to the existence of hydrophilic functional groups on the surface of the nanoparticles (Etemadi et al, 2017b;Kivi et al, 2019). Membranes with 0.75 wt.% of NPs showed the minimum contact angles.…”
Section: Hydrophilicity and Porositymentioning
confidence: 98%
“…Membrane bioreactors (MBRs) have recently received a lot of attention as an effective method for municipal and industrial wastewater treatment. MBRs bring excellent effluent quality at a relatively small plant footprint, in comparison with other prospects (Beygmohammdi et al, 2020;Kivi et al, 2019;Meng et al, 2017). Superior quality of the effluent obtained from the MBR process provides an alternative water source using wastewater treatment.…”
mentioning
confidence: 99%
“…The neat PSf membrane exhibited a higher contact angle (83.10 o ) and lower flux recovery ratio (FRR) (28.89%), while the functionalized membrane revealed higher FRR (58.93%) and improved hydrophilicity (contact angle 76.44 o ). In sequence, they reported improved FRR in their other study carried out by Kivi et al 117 wherein nanodiamond nanoparticles were modified using two approaches viz. thermal carboxylation (ND-COOH) and grafting with polyethylene glycol (ND-PEG) and then used in preparing HDPE composite membrane for enhanced MBR system performance.…”
Section: Nanoparticles Membrane Bioreactor (Nps-mbr)mentioning
confidence: 86%
“…Tizchang et al prepared silanized nanodiamond nanoparticles intercalated PSF membranes that exhibited higher flux recovery ratio (FRR) (58.93%) and improved hydrophilicity (contact angle 76.44°) [ 12 ]. Kivi et al prepared a HDPE composite membrane for enhanced MBR performance, which exhibited higher FRR of 77.9% compared to 61.7% for the bare membrane [ 13 ]. Many studies have shown that membrane fouling can be effectively controlled through electric field force or electroflocculation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%